Produção de hidrogênio verde no Maranhão: análise de potenciais áreas e da viabilidade técnico-econômica - FIGUEIREDO, Luiz Gustavo Rodrigues (2025)
Hydrogen plays an increasingly important role as an energy carrier in global decarbonization efforts. Its production through electrolysis, a technique that uses electrical energy to dissociate water into H2(g) and O2(g), presents a sustainable solution when coupled with renewable energy sources such as wind and solar. This study analyzes the potential for Green Hydrogen (GH) generation in the state of Maranhão, Brazil, through the implementation of a hydrogen plant with an installed capacity of 90 MW, capable of generating 13,365 tons of GH annually over a 22-year period. Two water sourcing options are considered: seawater and river water, from locations with the highest availability of this resource in the state, while taking into account the existing logistics and infrastructure for each site. Additionally, two renewable energy plants — wind and solar — are proposed, each supplying 50 % of the total energy demand (699.24 GWh/year) from the highest potential generation areas in the state for each source, to supply the demand of the plant connected to the National Interconnected System (SIN). Based on these premises, the results indicate significant potential for the implementation of this technology in the region. The calculations show that the cost of H2V production in São Luís/MA would be US$ 3.54/kgH2V, with a selling price of US$ 4.50/kgH2V to make the project attractive to investors, considering a Minimum Attractive Rate (TMA) of 10 % and a maximum payback of 12 years. In Bacabeira/MA, the production cost would be US$ 3.39/kgH2V, with a selling price of US$ 3.50/kgH2V. The pricing calculation methodology indicated that electricity is the most significant component for determining the hydrogen cost in Maranhão (83.5 %), and it is in this input where the greatest potential for cost reduction is found.